Digital Deception and Agenda Setting: A Qualitative Analysis of Fake News, False Narratives and Misinformation in TLP’S Aqsa March on Social Media (Journal of Social Sciences Review, 2025)
The undertaken research explored the perpetuation of fake news and misinformation trends as strategic tools of agenda setting and negative propaganda in digital political landscape of Pakistan analyzing social media content in the recent Al Aqsa march of TLP. The study has adopted qualitative research design to interpret the emotional narratives, misinformation, online trends in the light of agenda setting and framing theories. The study adopted qualitative research design for content analysis of viral Facebook and X posts during protest to identify key patterns of digital agenda setting, narrative construction, religious framing and emotional mobilization through fake news, disinformation and misinformation. The findings concluded that misinformation was not limited merely to distorted images and facts yet they were part of strategic AI powered campaigns of computational propaganda by multiple sides. All the stakeholders used digital spaces for propagation of false narratives to frame themselves as victims in order to gain public support. The information vacuum and weapnization of digital spaces intensified the situation which later on turned into a volatile law and order situation.
Keywords: Fake News; TLP; Agenda Setting; Framing; Religious Cues; Powered Computational Propaganda; False Narratives